1994
DOI: 10.1136/vr.134.16.415
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different Rose Bengal and complement fixation antigens for the diagnosis of Brucella melitensis infection in sheep and goats

Abstract: Fifteen different Rose Bengal antigens showed large differences with respect to pH, cell concentration and agglutination with the international standard anti-Brucella abortus serum, demonstrating the lack of international standardisation. Their sensitivity and specificity, compared with that of the complement fixation test, were evaluated for the diagnosis of B melitensis infection in culture-positive sheep, brucella-free ewes, and sheep and goats belonging to field flocks under different epidemiological condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
1
9

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 0 publications
8
87
1
9
Order By: Relevance
“…As in other EU countries [4], in the current B. melitensis eradication programme conducted in Portugal, a relatively high percentage of sheep which are negative in the RB screening test but positive in the CF confirmatory test has been identified. Tables II and III, figures as high as 3% (in infected animals) and 7% (in suspected animals) resulted in RB negative but CF positive.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…As in other EU countries [4], in the current B. melitensis eradication programme conducted in Portugal, a relatively high percentage of sheep which are negative in the RB screening test but positive in the CF confirmatory test has been identified. Tables II and III, figures as high as 3% (in infected animals) and 7% (in suspected animals) resulted in RB negative but CF positive.…”
Section: Discussionmentioning
confidence: 64%
“…However, it has been reported that a relatively high proportion of sheep and goats from B. melitensis-infected flocks show negative results in the standard RB test but positive in the CF test, questioning the sensitivity of the former as a screening test [4]. Thus, the simultaneous use of both is recommended to obtain a maximal sensitivity [4,12].…”
Section: B Abortus and B Melitensis Infectionsmentioning
confidence: 99%
See 3 more Smart Citations